STRATEGI PELAYANAN KONSULTAN PAJAK DALAM MENCAPAI KEPATUHAN KEWAJIBAN PERPAJAKAN PADA PERUSAHAAN DAGANG KOTA BANDUNG - Mujiyanti, Putri Eka; Dwirini, Dwirini (Institut Rahmaniyah Sekayu, 2024)
Taxes, which are one source of income for the state to carry out development, will continue to grow when this income increases every year. The role of tax consultants in achieving compliance with tax obligations is very important. There are many benefits for users of tax consultant services. The method used in this research is qualitative with a qualitative descriptive research type. This is intended to obtain a descriptive picture of the problems in this research. This research uses data collection techniques through observation, interviews and document searches. There were several informants involved in this research. The informant is a tax consultant and a trading company in Bandung. The results of the research show that the presence of tax consultants is very necessary for trading companies that do not understand taxation. There are also many challenges faced by a tax consultant in current tax developments. The benefits felt by trading companies when using tax consultant services can make companies more tax aware and comply with tax obligations properly according to applicable regulations. Taxpayers previously felt many obstacles, with a tax consultant they will feel very helped.